Open Science Policies seen from the perspective of researchers’ communities - Manco, Alejandra (Septentrio Conference Series, 2022)
During the last ten years, many institutions have begun to design, adopt, and implement open science policies (Schmidt et al., 2018; Kretser et al., 2019). Nevertheless, there is a research gap in tackling how these policies impact researchers' knowledge production. Therefore, this research investigates the researcher's opinions, perceptions, and experiences with open science policies concerning knowledge production processes from researchers from Brazil, France and Peru. It aims to highlight differences and similarities in the science disciplines across these countries. Furthermore, it aims to provide an overview of how communities of researchers from the sciences – physics, chemistry, and biology – visualize open science policies, meaning their opinion and discourse on this subject and whether their knowledge production processes have changed and to what extent they had an impact on their research products.